Early deprivation, atypical brain development, and internalizing symptoms in late childhood. (7th February 2017) - Bick, J.; Fox, N.; Zeanah, C.; Nelson, C.A.
Highlights: We examined neural substrates of risk for internalizing symptoms in institutionally reared youth. Internalizing symptoms were elevated in children with histories of institutional rearing. Institutional rearing was associated with alterations in white matter throughout the brain. Tracts implicated in emotional development predicted risk for internalizing symptoms. The external capsule and body of the corpus callosum were significant mediators. Abstract: Children exposed to extreme early-life neglect such as in institutional rearing are at heightened risk for developing depression and anxiety disorders, and internalizing problems more broadly. These outcomes are believed to be due to alterations in the development of neural circuitry that supports emotion regulation. The specific neurodevelopmental changes that contribute to these difficulties are largely unknown. This study examined whether microstructural alterations in white matter pathways predicted long-term risk for internalizing problems in institutionally reared children. Data from 69 children were drawn from the Bucharest Early Intervention Project, a randomized clinical trial of foster care for institutionally reared children. White matter was assessed using diffusion tensor imaging (DTI) when children were between 8 and 10 years of age. Internalizing symptoms were assessed at the time of the MRI scan, and once children reached 12–14 years of age. Results indicated that neglect-associated alterations in the external capsule and corpus callosum partially explained links between institutional rearing status and internalizing symptoms in middle childhood and early adolescence. Findings shed light on neural mechanisms contributing to increased risk for emotional difficulties among children reared in adverse conditions and have implications for prevention and intervention.